The Influence Of Health Education About Infant Massage On Mother's Knowledge And Skill In Massageing Baby Independently In Karya Jaya Kota Tebing Tinggi In 2022 - Nila Hayati (Sean Institute, 2023)
Baby massage is a massage that is carried out closer to smooth strokes on the surface of the skin to produce an effect on the nerves, muscles, and respiratory system and facilitate blood circulation. Baby massage requires mother's knowledge and skills in doing massage. Mother's knowledge and skills in the implementation of infant massage are still relatively low. This study aims to determine the effect of Health Education on Infant Massage on Mother's Knowledge and Skills in Independently Massaging Babies in Karya Jaya Village, Tebing Tinggi City in 2022. This research is a pre-experimental research with one group pretest-posttest design approach. This research was carried out from September 12, 2022 to October 1, 2022. The population was 62 people. Sampling using purposive sampling with a total sample of 26 people. The results showed that before being given health education, the majority of mothers' knowledge of massaging babies was sufficient and the majority of mothers' skills in massaging babies independently were less skilled and after being given health education, the majority of mothers' knowledge of massaging babies was sufficient and the majority of mothers' skills in massaging babies independently. is skilled. Based on the results of the Wilcoxon Signed Test, it was found that the mother's knowledge (p = 0.001 <0.05) and mother's skills (p = 0.014<0.05). The conclusion in this study is the Effect of Health Education on Infant Massage on Mother's Knowledge and Skills in Massaging Babies Independently in Karya Jaya Village, Tebing Tinggi City in 2022. Suggestions in this study are Karya Jaya Village, Tebing Tinggi City provide adequate education to increase maternal knowledge and mother's skill in doing baby massage.